2015
DOI: 10.1109/tmi.2014.2344911
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Nonrigid Registration Error Detection Algorithm Using Clinical MRI Brain Data

Abstract: Identification of error in non-rigid registration is a critical problem in the medical image processing community. We recently proposed an algorithm that we call “Assessing Quality Using Image Registration Circuits” (AQUIRC) to identify non-rigid registration errors and have tested its performance using simulated cases. In this article, we extend our previous work to assess AQUIRC’s ability to detect local non-rigid registration errors and validate it quantitatively at specific clinical landmarks, namely the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…These estimations can be evaluated through ground-truth local-error magnitudes for experiments for which those are known. This allows for a comparison with AQUIRC, 19,20 which computes a dimensionless measure of local error magnitude based on (3,0)-consistency. We used our own implementation of their technique, the results of which were presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These estimations can be evaluated through ground-truth local-error magnitudes for experiments for which those are known. This allows for a comparison with AQUIRC, 19,20 which computes a dimensionless measure of local error magnitude based on (3,0)-consistency. We used our own implementation of their technique, the results of which were presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…4.5. We also compare our method to our own implementation of assessing quality using image registration circuits (AQUIRC), 19,20 which computes a dimensionless measure of local registration error magnitude which can be correlated with the true local error magnitudes. It is observed that the magnitude of the updates computed by CBRR correlate substantially stronger with the true error magnitudes in comparison to AQUIRC.…”
Section: -D Mr Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantifying the error in correspondence as a result of NRR in a target image is a challenging problem, with some calling automatic registration techniques impossible to validate[5]. Datteri et al have developed the AQUIRC (Assessing Quality Using Image Registration Circuits)[6, 7] model to assess registration quality is target images using registration circuits. The authors proposed to use registration circuits to model the local error associated with NRR and have shown moderate success in applying this to multi-atlas segmentation[8].…”
Section: Introductionmentioning
confidence: 99%